Antileishmanial activities of caffeic acid phenethyl ester loaded PLGA nanoparticles against Leishmania infantum promastigotes and amastigotes in vitro - Abamor, Emrah Sefik (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Objective To investigate and compare the antileishmanial effects of CAPE and (CAPE)(PLGA) (NPs) on Leishmania infantum (L. infantum) promastigotes and amastigotes in vitro. Methods Efficacies of CAPE, (CAPE)(PLGA) (NPs) and free PLGA nanoparticles (NPs) on promastigotes were evaluated using MTT and promastigote count assays, and their anti-amastigote effects were determined via infection index analysis. Griess reaction was also performed to calculate nitric oxide production of macrophages exposed to investigated molecules. Results It was determined that CAPE and (CAPE)(PLGA) (NPs) demonstrated significant inhibitory effects on L. infantum promastigotes and amastigotes, while free NPs did not exhibit any meaningful antileishmanial effectiveness. The IC50 values of CAPE for L. infantum promastigotes and amastigotes were assessed as (51.0 +/- 0.8) and (19.0 +/- 1.4) mu g/mL, respectively (P<0.05). On the other side, it was revealed that (CAPE)(PLGA) (NPs) had superior antileishmanial activity on both forms of parasites since its IC50 values for L. infantum promastigotes and amastigotes were (32.0 +/- 1.3) and (8.0 +/- 0.9) mu g/mL, respectively (P<0.05). It was also determined that both agents strongly stimulated nitric oxide production of macrophages. Conclusions The obtained results show that (CAPE)(PLGA) (NPs) have a great potential to be especially used in treatment of visceral leishmaniasis; however, in vivo antileishmanial screening of these molecules should be performed in the near future.
Keywords: Leishmania; CAPE; Nanoparticles; PLGA; Antileishmanial; DRUG-DELIVERY; ANTIBACTERIAL ACTIVITY; PROPOLIS; RELEASE; FORMULATION; INFECTIONS; COMPONENTS; INHIBITION; EMERGENCE; MECHANISM; Public, Environmental & Occupational Health; Tropical Medicine